Design of a Circular Disc Microstrip Antenna Loaded By Annular Ring - شعبان, رائد مسلم (University of Thi-Qar Journal of Science, 2014)
The research contained in this thesis is a theoretical study of antenna design and calculation of the radiation fields using electric fields integral equation (EFIE) and magnetic field integral equation (MFIE). These equation have been converted, using the method of moments formulation of electromagnetic radiation in this these based onthe bodies of revolution (BoR),which are generated by revolution a planar curve about an axis  called axis of symmetry. To find an unknown electric current density  on the surface of the conductor ,and both unknowns electric and magnetic density  current on the surface of the dielectric which are  responsible for the generation of radiationfields in the space for the components (Eθ ,Eφ) ,the surface currents was represented by a set of basis functions that give the Fourier series because the body has a circular symmetry property and then select a set of weighted  functions to find a linear system by using Galerkin  method which requires that the weighted functions are equal to the complex  conjugate of the current  JW = )( *  .